An Example of Nonexistence of $κ$-Solutions to the Ricci Flow (Journal of Mathematical Study, 2018)
In this paper,we construct an example of three-dimensional complete smooth $κ$-noncollapsed manifold, which admits no short time smooth complete and $κ$-noncollapsed solutions to the Ricci flow.
Keywords: Ricci flow; nonexistence.